2014
DOI: 10.1021/jo5013459
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Rate Constants for Hydrogen Atom Transfer from Tertiary Amides to the Cumyloxyl Radical: Evaluating the Role of Stereoelectronic Effects

Abstract: Access and use of this website and the material on it are subject to the Terms and Conditions set forth at Absolute rate constants for hydrogen atom transfer from tertiary amides to the cumyloxyl radical: evaluating the role of stereoelectronic effects Salamone, Michela; Milan, Michela; Dilabio, Gino A.; Bietti, Massimo http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=fr L'accès à ce site Web et l'utilisation de son contenu sont assujettis aux conditions présentées dans le site LISEZ CES COND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 64 publications
(82 reference statements)
4
51
0
Order By: Relevance
“…This may, for example, include the water‐mediated isomerization of the benzyloxyl radical ( 4 ) to the hydroxybenzyl radical through a formal 1,2‐hydrogen shift (not shown) . The relevance of this pathway will, among other things, depend on the polarity of the surrounding solvent and its ability to engage in hydrogen‐bonding interactions with the radical 4 . For the sake of completeness, it should also be mentioned that the toluene shown in Figure as an active reaction partner can potentially also “solvate” the hydroperoxide 3 while it undergoes O−O bond homolysis and then react with the generated HO .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may, for example, include the water‐mediated isomerization of the benzyloxyl radical ( 4 ) to the hydroxybenzyl radical through a formal 1,2‐hydrogen shift (not shown) . The relevance of this pathway will, among other things, depend on the polarity of the surrounding solvent and its ability to engage in hydrogen‐bonding interactions with the radical 4 . For the sake of completeness, it should also be mentioned that the toluene shown in Figure as an active reaction partner can potentially also “solvate” the hydroperoxide 3 while it undergoes O−O bond homolysis and then react with the generated HO .…”
Section: Resultsmentioning
confidence: 99%
“…[43][44][45] The relevance of this pathway will, among other things,d epend on the polarity of the surrounding solventa nd its ability to engage in hydrogen-bonding interactions with the radical 4. [46][47][48][49][50] For the sake of completeness, it should also be mentioned that the toluenes hown in Figure 3a sa na ctive reaction partner can potentially also "solvate" the hydroperoxide 3 while it undergoes OÀOb ond homolysis and then react with the generated HOC radicali nas econd step along the lines shown in Figure 2. This pathway has been studied by using the same theoretical approach as above and shown to be enthalpically inferior to the sequence shown in Figure 3( see the Supporting Information for furtherd etails).…”
Section: Reaction Of Benzylhydroperoxide With Toluenementioning
confidence: 99%
“…[35] Niu, Li and co-workers [36] were the first to demonstrate the significance of this for alcohol oxidation. Using model FeO/Pt (111) and Cu 2 O/Ag (111) catalysts, the authors demonstrated with STM and DFT measurements that activated oxygen, originating from facile O 2 dissociation at interfacial sites, promoted alcohol adsorption and OÀ H bond activation. Furthermore, the authors elegantly demonstrated that these interfacial effects were independent of particle size (Figure 2-B).…”
Section: Mark Douthwaite Is a Postdoctoral Research Associate At The Cardiff Catalysis Institute Under The Supervision Of Professors Grahmentioning
confidence: 99%
“…The mechanism of HAT processes was investigated in many works (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54). Of special interest are the studies by Mayer and co-authors (43-47) with a systematic analysis of these processes in terms of the BEP relationship.…”
Section: Hydrogen Atom Transfer In Oxidation Reactions On Metal Complmentioning
confidence: 99%